HUBUNGAN FREKUENSI SEKSUAL TERHADAP KEJADIAN BPH DI RUMAHSAKIT UMUM DAERAH KABUPATEN KEBUMEN - tri sujiyati; handoyo -; safrudin ANS (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2010)
Currently, the increasing of BPH (Benigna Prostat Hypertrofy) incident is caused by many faktors, such as, age, diet and ras. However other factors could predict caused of BPH such as sexual frequency. Therefore, this research focus on the incident of BPH towards sexual frequency. The objective of research was to find out correlation between sexual frequency with BPH incident in General Hospital, Kebumen regency. The design used in the research was deskriptif quantitatif design with cross sectional approach. The samples of the study were 24 respondents with inclusion and exclusion criteria. The date were analized by using product moment test to find out wether there was correlation between the variables. Research finding showed that probability (sig) 0,455>0,05 and coefisien correlation is -0,160, it could be concluded there was no significant correlation between sexual frequency with BPH incident in General Hospital, Kebumen Regency Keywords : BPH. Sexsual frequency